Use of acetaminophen in young subelite athletes - Garcin, M.; Mille-Hamard, L.; Billat, V.; Imbenotte, M.; Humbert, L.; Lhermitte, Z. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: The purpose of the present investigation was to look for other drugs besides doping substances in the urine of subelite athletes submitted to heavy training. Methods. One hundred and forty-one young subelite athletes (in sprint, cycling, middle distance running and handball) were included in the study, with a control group of 89 high school pupils. Drugs were researched by high performance liquid chromatography using a diode array detector. Results: Among the 212 subjects who agreed to give a urine sample, acetaminophen was detected: 9.5% for the subelite athletes versus 1.3% for the control group with a greater difference for sprint and cycling training (26.7% and 20%, respectively). Acetaminophen is used to treat both acute and chronic pains. It relieves pain by elevating the pain threshold. Conclusion: The use of acetaminophen has to be taken into account by medical staff, trainers and educators.